Penerapan Standar Keamanan pada Proses Pengelasan Industri Skala Kecil di Desa Balak Kecamatan Songgon - Fita Lestari, Riska; Ratna Mustika Yasi; Adi Mulyadi; Lutfi Irawan Rahmat; Agus Priyanto; Muhamad Khoirul Anam (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
This article discusses safety regulations during the welding process to reduce the risk of workplace accidents, long-term health consequences, and improve the quality of finished products. The study examines various international safety regulations, practical safety measures, and incidents involving welding. An important first step in increasing employee awareness and understanding of the potential risks that may arise during the welding process is safety socialization. Risks associated with welding include exposure to UV light, hazardous gases, sparks and high temperatures, which, if not managed appropriately, can jeopardize worker health and safety. Therefore, to ensure the best possible implementation of occupational safety standards, organized teaching initiatives through outreach are required. Personal protective equipment (PPE), safe work practices, handling of dangerous goods, risk mitigation and emergency response training are examples of socialization activities. A thorough understanding of welding safety is believed to reduce the number of workplace accidents, increase output, and make the workplace safer. This community service focuses on conducting welding and work safety training for home welding workshop businesses in Balak Village, Songgon District, Banyuwangi Regency. The application of safety standards to the welding process aims to evaluate the effectiveness of welding safety socialization in improving workers' compliance with safety procedures, while providing recommendations for optimizing future training programs.